Inactivation of coliform bacteria in Black Sea waters due to solar radiation - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
The effects of solar radiation and temperature on bacterial die-off rates in Black Sea coastal waters using total coliform as the indicator organism were studied. Coliform die-off experiments were carried out in seawater samples collected along the coastline. The experiments were conducted in beakers filled with seawater that were kept at constant temperatures and exposed to solar radiation. The membrane filter technique was used for the coliform analysis. Temperature ranging between 9 and 26 degreesC and solar radiation between 20 and 60 cal/cm(2) h were tested. Experiments in the dark were also conducted to isolate the effect of solar radiation from the other factors and, furthermore, to determine the effect of temperature on bacterial die-off. The solar radiation was found to be the most significant factor affecting the mortality of coliform bacteria. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: bacteria; black sea; coliform; inactivation; solar radiation; temperature; WASTE STABILIZATION PONDS; ENVIRONMENTAL-FACTORS; ENTERIC BACTERIA; SURVIVAL; SUNLIGHT; SEAWATER; RATES